Saving Legs & Lives: the efficacy of a community-based cardiovascular rehabilitation programme versus usual care on exercise capacity and quality of life in patients who have undergone lower limb revascularisation for peripheral arterial disease—protocol for a single-centre randomised-controlled trial - Norman Morris; Tony Stanton; Tuppence Richman; Kim Greaves; Jill O’Donnell; Krist Feka; Pankaj Jha; Michelle Aust; Joseph J. Scott; Mia Schaumberg; Christopher D. Askew; Saving Legs & Lives Trial Group; et al. (BMJ Open)
Introduction Peripheral artery disease (PAD) is an atherosclerotic condition characterised by stenosis or occlusion of the arteries in the lower limbs. Patients with PAD commonly report intermittent claudication (leg pain/discomfort) during physical activities, which significantly limits the ability to walk and perform activities of daily living. Supervised exercise training is an effective therapy that can improve walking capacity in people with PAD. Emerging evidence also suggests that supervised exercise therapy following lower limb revascularisation can further enhance walking capacity when compared with revascularisation alone. However, access to dedicated exercise programmes for patients with PAD is limited in most countries, and there is a need to test the efficacy of alternative rehabilitation strategies and referral pathways. This randomised-controlled study aims to assess the efficacy of a cardiovascular rehabilitation (CR) programme versus usual care on walking capacity and quality of life in patients who have undergone lower limb revascularisation for PAD.Methods and analysis This will be a single-centre, prospective, parallel group, randomised-controlled trial. Sixty-six participants who have undergone a lower limb revascularisation procedure for PAD, in the previous 12 months, will be randomly allocated to a CR programme or a usual care (control) group. The CR programme will include two supervised exercise sessions per week for 6 weeks primarily consisting of intermittent treadmill walking at a moderate exercise intensity and home-based walking advice. During the 6-week programme, participants will also attend one education seminar (5.5 hours) which will cover topics such as diet, medications, exercise training and lifestyle modifications for the management of cardiovascular diseases. The control group will receive usual care and medical advice from their local doctor and vascular surgeon. The primary outcome will be 6-min walk distance. Secondary outcomes include pain-free walking distance during the six-minute walk test, maximal and pain-free walking time during a graded treadmill walking test, cardiorespiratory fitness, self-reported walking capacity, disease-specific quality of life, and self-reported and objectively measured physical activity levels. Exploratory outcomes include brachial artery flow-mediated dilation, arterial stiffness, ankle-brachial blood pressure index and biomarkers of cardiovascular disease risk. Outcomes will be assessed at baseline (week 1), following the CR/usual care period (week 8) and again at 6-month follow-up (week 34).Ethics and dissemination This study has received ethics approval from the Human Research Ethics Committees of Queensland Health Metro North Hospital and Health Service (94155) and the University of the Sunshine Coast (S231914). Findings from this study will be disseminated in peer-reviewed journals and through national and international conference presentations.Trial registration number ACTRN12623000190606.